Riding the dragon: Ascent of China's Renminbi and the decline of dollar dominance - Nilanjan Banik; Khanindra Ch. Das (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2024)
Several commentaries are written about de-dollarization. We analyze the factors which are contributing to de-dollarization and provide an alternative assessment. On the economic front, the US economy's reduced fiscal and financial capacity can strain economic trust in the dollar. The internationalization of the Chinese currency is another factor. Additionally, a lower forecast for the world economic growth outlook, a higher debt financing in the US and a war in Europe are also leading to central banks around the world buying more gold and reducing investment in the US treasury bonds. While these factors may lead to a reduced demand for dollars and increase the use of alternate international currencies, including digital currencies, we argue that dislodging the dollar as a global anchor currency is going to be restricted by economic and geopolitical reasons.
hdl:20.500.12870/7235
Keywords: H6; O5; 330; De-dollarization; Twin Deficits; CBDC